The Necessity of Death and its Purpose from the Point of View of Sadr Ol-Muta'allehinShirazi - naser mohammadi (حکمت اسرا)
Why is death one of the essential things in this world? To what end and on the basis of what wisdom does death occur? And why is death defined in the evolutionary system? MullaSadra has examined the necessity of natural death from the perspective of the intrinsic ultimate cause of death. In other words, with the evolution of the soul from material life to the Hereafter, the death of the body is a necessity to the subsequent transcendental necessity. Therefore, the intrinsic ultimate cause of death is the evolution of the soul, one of the functions and consequences of which is the leaving of the body by the soul and the death of the body. In the event of the death of the body and the death of souls, other complications will inevitably arise, such as the possibility of the emergence of other human beings or the lack of cruelty of the pious, other than that some have mistakenly considered them to be the inherent end of death. Thus, the cause of imminent death is the soul and its evolution.Unlikely actual cause of death is the Angel of death and other real causes of death. According to MullaSadra, the cessation of the force of Growth and Faculty, which are discussed in the natural sciences, are the underlying causes of death and are weak and convincing reasons, and they themselves can be justified by the inherent ultimate cause